2013
DOI: 10.1038/jhg.2012.124
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study of a coronary artery disease risk variant

Abstract: Although over 30 common genetic susceptibility loci have been identified to be independently associated with coronary artery disease (CAD) risk through genome-wide association studies (GWAS), genetic risk variants reported to date explain only a small fraction of heritability. To identify novel susceptibility variants for CAD and confirm those previously identified in European population, GWAS and a replication study were performed in the Koreans and Japanese. In the discovery stage, we genotyped 2123 cases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 30 publications
(28 reference statements)
6
86
0
Order By: Relevance
“…In 2007, three groups independently reported the first region of the genome to be linked to CAD utilizing the GWAS approach (46)(47)(48) Chinese, Korean, or Japanese subjects, with at least 6 of these loci overlapping with loci uncovered in Europeans (63)(64)(65)(66)(67). Thus, both ethnic-specific as well as cross-ethnic loci have been uncovered to date.…”
Section: Discovery Of the First Locus Predisposing To Common Presentamentioning
confidence: 99%
“…In 2007, three groups independently reported the first region of the genome to be linked to CAD utilizing the GWAS approach (46)(47)(48) Chinese, Korean, or Japanese subjects, with at least 6 of these loci overlapping with loci uncovered in Europeans (63)(64)(65)(66)(67). Thus, both ethnic-specific as well as cross-ethnic loci have been uncovered to date.…”
Section: Discovery Of the First Locus Predisposing To Common Presentamentioning
confidence: 99%
“…These populations were listed as separate data sets; all data were extracted independently by two reviewers according to the inclusion criteria. All the consistent datasets by reviewers were Samani et al, 2007;Huang et al, 2008;Muendlein et al, 2009;MIGen Consortium, 2009;Wang et al, 2011;Xie et al, 2011;Guo et al, 2011;Ellis et al, 2011;Gigante et al, 2012;Esparragón et al, 2012;Lee et al, 2013. Discrepancies were recorded and solved by discussion with a third reviewer.…”
Section: Study Populationsmentioning
confidence: 99%
“…Finally, 12 studies (17,766 patients and 20,272 controls) were included in this meta-analysis. Of these, 2 studies were performed in Oceania (Ellis et al, 2011), 7 in Europe and America (Samani et al, 2007;Muendlein et al, 2009;MIGen Consortium et al, 2009;Wang et al, 2011;Gigante et al, 2012;Esparragón et al, 2012), and 4 in Asia (Huang et al, 2008;Xie et al, 2011;Guo et al, 2011;Lee et al, 2013) (Figure 1 …”
Section: Literature Search and Databases For Meta-analysismentioning
confidence: 99%
“…GWAS represent an essentially unbiased approach capable of simultaneously assessing thousands of genetic variants across the whole genome for association with CAD or H. pylori infection. To date, multiple GWAS have identified >50 common genetic susceptibility loci independently associated with CAD (41)(42)(43)(44). Two studies identified four single nucleotide polymorphisms (SNPs: rs4833095, rs10004195, rs368433 and rs10502974) located in different genes that were associated with H. pylori infection using GWAS (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…CAD and H. pylori infection could potentially share common factors of genetic susceptibility. Genetic loci associated with host susceptibility to CAD or H. pylori infection have been identified using genome-wide association studies (GWAS) in recent years (41)(42)(43)(44)(45)(46). GWAS represent an essentially unbiased approach capable of simultaneously assessing thousands of genetic variants across the whole genome for association with CAD or H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%